Analisis Manajemen Program Mujahadah dan Pembibitan Tahfizhul Qur’an - Doni Susanto (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims not only to assist students in achieving or improving the quality of memorizing the Al-Qur'an, which they mastered while studying at the Aliyah madrasah, but also to prepare alumni who will be able to continue their studies abroad, knowledgeable but adhering to the